Control, compliance and conformity at the University of Fort Hare 1916 - 2000: a Gramscian approach - Johnson, Pamela (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2014)
Arising from Marxist theory, critical theory investigates the mechanisms that enable continued domination in capitalist society, with a view to revealing the real, but obscured, nature of social relations and enabling these to be challenged by subjugated classes. Within the broad spectrum of Marxist theory, social relations of domination and subordination are assigned according to the relationship of social classes to economic production. However, the neo-Marxist perspective developed by Antonio Gramsci locates relations of power within the broader context of the political economy. In doing so, the role of the State in a capitalist society assumes greater significance than that of maintaining and securing social relations on behalf of the dominant class through coercion and force. Instead, the State embarks on a range of activities in the attempted "exercise of hegemony" , or the cultivation of general acceptance by all social classes of existing social relations and conditions. Gramsci refers to this desired outcome as "consent" , the product of the successful exercise of hegemony, a political function which is thus crucial to the accumulation of capital. When unsuccessful, dissent cannot be contained by the State, and the extent to which contestation constitutes a threat is revealed by recourse to coercion. The manner in which relations of power are cemented through the exercise of hegemony lies at the core of this thesis. It investigates the relationship between the State and the administrators of an institution within civil society, the University of Fort Hare, as well as the responses to the activities of the State and University Administration within the University itself, over an extended period of time between 1916 and 2000. This period is divided into three specific time frames, according to changes in the expression of the South African State. In general, it is seen that conformity characterises the relationship between the State and the University Administration, underscoring the success of the State in fostering the role of education in the reproduction of social relations and values and in eliciting conformity. The nature of conformity is seen to vary according to different expressions of the State and changes in social relations, which are in turn informed by the overarching political economy and events taking place within society and the University of Fort Hare. Manifestations of consent and dissent, as responses to the attempted exercise of hegemony, are presented in the three periods corresponding to different expressions of the State. Four reasons for conformity, as presented by Gramscian scholar Joseph V Femia (1981), are utilised in order to explain and illustrate the nature of control and compliance at the University of Fort Hare between 1916 and 2000.
Keywords: University of Fort Hare -- History; University of Fort Hare -- Administration; Higher education and state -- South Africa; Hegemony -- South Africa; Conformity -- Political aspects -- South Africa; Abuse of administrative power -- South Africa; Education, Higher -- South Africa -- Eastern Cape; South Africa -- Politics and government -- 1916-2000; Apartheid -- South Africa